The Role of Communication in Work-Life Balance: A Study of Female Employees at a Religious Institution - Hartati, Novia Sry; Rubino; Indra, Farhan (Yayasan Ilomata, 2024)
The objective of this research is to conduct a communication analysis of female employees of the Medan City Office of the Ministry of Religious Affairs in order to ascertain how they maintain a balance between their professional and familial responsibilities. The objective is to analyse and identify the family communication model and the impact of communication on female employees in maintaining work-life balance. The research approach employed is qualitative, with the objective of obtaining an in-depth description of the data. The data were obtained through in-depth interviews and an analysis of relevant documentation. In-depth interviews were conducted in an unstructured format with female employees of the Medan City Ministry of Religion Office, while documentation was employed to collect data that would supplement the research results. The findings indicate that the linear communication model, the interactional communication model, the transactional communication model, and the constructive communication model are effective communication strategies in specific contexts where communication between a husband and a wife in a family is required to be conveyed in a clear and targeted manner. These communication approaches are dialogic and collaborative in nature, which allows families to reach a common understanding and develop shared values. This contributes to the strengthening of familial cohesion and facilitates the balance between work and family life.